Keyboard harmony or partimento as a methodological strategy for teaching improvisation and learning musical language (2016)
The intention behind this article is to present and provide a methodological alternative to teach musical improvisation in an academic context in which classical or academic so-called music is transmitted or taught. This approach covers the basis for the realization of the parting and the continuous bass, goes through Romanticism and reaches the rudiments or foundations of the language of jazz, which is a very effective tool to build a connecting bridge between musical traditions (the original academic music European and jazz) and understand French impressionism of the late 19th century. Behind this approach to the teaching of harmony on the keyboard is the interest in establishing improvisation as an essential element for the training of the academic musician and, if it is not to be an attainable goal in the short term, state the benefits that implies an accelerated appropriation of musical language.